PERAN DIGITAL PARENTING DALAM MENUMBUHKAN NILAI-NILAI KARAKTER ANAK USIA 5-6 TAHUN PADA KELUARGA GENERASI MILENIAL - Aulia, Meirantie; Asep Kurnia Jayadinata (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has significantly influenced parenting practices among millennial families. This study aimed to analyze the effect of digital parenting on the character values of children aged 5–6 years. A quantitative approach with a cross-sectional survey design was employed involving 60 parents of children aged 5–6 years at TK Qurrota A’yun, Bandung Regency. Data were collected through questionnaires measuring digital parenting practices and children’s character values, including discipline, responsibility, independence, honesty, and social care. Data were analyzed using descriptive statistics and simple linear regression. The findings revealed that the level of digital parenting was categorized as moderate to high, while children’s character values were categorized as fairly good. Regression analysis showed that digital parenting had a positive and significant effect on children’s character values, with a significance value of 0.000 and a contribution of 28.9%. These findings indicate that parental guidance, supervision, and role modeling in the use of digital technology play an important role in fostering positive character development among young children in the digital era.